2006
DOI: 10.1007/s10549-006-9364-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair polymorphisms might contribute differentially on familial and sporadic breast cancer susceptibility: a study on a Portuguese population

Abstract: The purpose of this study was to evaluate the role of polymorphisms in DNA repair genes as genetic indicators of susceptibility to familial and sporadic breast cancer. We analysed DNA samples from 285 breast cancer patients and 442 control subjects, for XRCC1 Arg399Gln, XPD Lys751Gln, RAD51 G135C and XRCC3 Thr241Met polymorphisms using PCR-RFLP. We observed that women carriers of XRCC1 399Gln genotypes and without family history of breast cancer have a protective effect concerning this disease (OR = 0.54 95% C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 56 publications
4
65
1
Order By: Relevance
“…no reporting of the relevant genotype frequencies, whereas the other [18] was excluded for examining the association between other XRCC3 polymorphisms and premenopausal breast cancer risk). As a result, 19 case-control articles [2,3,5,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]] (23 case-control studies, considering that Breast Cancer Association Consortium has more than one studies included) were included in this meta-analysis; 20 case-control studies on non-Chinese subjects (19,575 cases and 21,125 controls) and three case-control studies [3,24,29] on Chinese subjects (1,216 cases and 1,112 controls). Table 1 presents in detail the results of the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…no reporting of the relevant genotype frequencies, whereas the other [18] was excluded for examining the association between other XRCC3 polymorphisms and premenopausal breast cancer risk). As a result, 19 case-control articles [2,3,5,12,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]] (23 case-control studies, considering that Breast Cancer Association Consortium has more than one studies included) were included in this meta-analysis; 20 case-control studies on non-Chinese subjects (19,575 cases and 21,125 controls) and three case-control studies [3,24,29] on Chinese subjects (1,216 cases and 1,112 controls). Table 1 presents in detail the results of the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Data of literature suggest that RAD51 gene 135G>C polymorphism may contribute to head and neck cancer and mammary carcinogenesis [11][12][13][14][15][16][17]. A study of women matched for BRCA1 mutation revealed that the C allele of this polymorphism is associated with a 2-fold reduction in the breast and ovarian cancer risk as compared with the wild-type G allele [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rs373572 was found to be a unique SNP located in the coding-region of RAD18 in the present study. RAD18 has several functional domains, including RING-finger motif [37] , zinc-finger motif [38] and E3 ubiquitin-ligase domain [39] . Because rs373572 is located in the E3 ubiquitin-ligase domain, it might affect the E3 ubiquitin-ligase activity of RAD18 and further influence the ubiquitination of PCNA and activation of TLS.…”
Section: Discussionmentioning
confidence: 99%